SEMANTIC FEATURES OF WORDS CONTAINING “竹 BAMBOO” IN CHINESE CHARACTERS - Ham, Pham Ngoc (VNU Journal of Foreign Studies; Vol 36 No 2, 2020)
As an ideographic and phonogramic writing system, Chinese characters vividly reflect human cognition about the real world and their life. This is evident in such canonical examples as Chinese characters that contain the symbol “竹” (bamboo). The article primarily uses common research methods, including statistical, descriptive, analytic methods, to examine the relationships between pictograms and semantics of Chinese characters containing “竹” (bamboo), clarify their semantic development as well as cultural implications. The paper hopes to contribute a reference for studying Chinese characters and teaching Chinese in Vietnam.